THE IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARDS, INTERNAL CONTROL SYSTEMS AND INFORMATION TECHNOLOGY UTILIZATION ON THE QUALITY OF LOCAL GOVERNMENT FINANCIAL STATEMENTS WITH ORGANIZATIONAL COMMITMENTS AS MODERATION VARIABLES - Suci - Atiningsih (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
The purpose of this study to determine the effect of the application of government accounting standards, internal control systems and the use of information technology on the quality of local government financial reports with organizational commitment as a moderating variable conducted in the Regional Government Work Unit (SKPD) of the Brebes Regency Government. The population in this study was 49 SKPD of the Brebes Regency Government. Sampling using a purposive sampling technique. The sample is the head of finance, treasurer and accounting staff. This research uses primary data. Data analysis uses the SmartPLS3.0 application. The results of this study are the application of accounting standards, internal control systems and the use of information technology have a positive effect on the quality of financial statements, organizational commitment is not able to moderate the influence of the application of accounting standards and internal control systems on the quality of financial statements of local governments, but organizational commitment is able to strengthen the influence of technology use information on the quality of local government financial reports.